Public Speaking in Islamic Pearching ( Da’wah) for Generation Z in The Digital Era - Sutinnarto; Choirunnisa; Muhammad Agung Setiawan; Lakna Tulas'un; Rif'atul Himmah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The development of digital technology has fundamentally transformed the landscape of Islamic da'wah, particularly in reaching Generation Z who have grown up as digital natives. This study aims to deeply understand how public speaking in da'wah for Generation Z in the digital era is practiced, experienced, and meaningfully interpreted by da'wah practitioners and recipients. This research employs a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with 15 informants consisting of Generation Z da'wah creators, Generation Z audiences, and da'wah public speaking practitioners, as well as observation of da'wah content on TikTok, Instagram, and YouTube platforms, and documentation. Data analysis used the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing. The findings reveal four main themes. First, there has been a paradigm shift in da'wah public speaking from a one-way, monological communication model toward a dialogical and participatory model. Generation Z preachers no longer position themselves as lecturers who lecture, but as dialogue partners who accompany audiences in the search for religious meaning. Second, five effective strategies used by da'wah creators were identified: relatable and personal storytelling, attractive visuals with short content, light humor as a door opener to the heart, authentic language that does not lecture, and interactivity that actively involves the audience. Third, the research identifies significant challenges faced, including the audience's short attention span, the risk of oversimplifying religious messages, algorithm dominance favoring entertainment content, and negative comments and attacks on social media. Fourth, Generation Z interprets good da'wah as da'wah that is touching, honest, and relevant to their daily lives, not da'wah that focuses solely on sin and threats.